Physiological and Biochemical Characteristics of Rainbow Trout with Severe, Moderate and Asymptomatic Course of Vibrio anguillarum Infection - Stanislav Rimaso Kurpe; Irina Viktorovna Sukhovskaya; Ekaterina Vitalyevna Borvinskaya; Alexey Anatolievich Morozov; Aleksey Nikolaevich Parshukov; Irina Evgenyevna Malysheva; Alina Valeryevna Vasileva; Natalia Alexandrovna Chechkova; Tamara Yurevna Kuchko (Animals, 2022)
This article describes the clinical manifestation of natural Vibrio anguillarum infection in rainbow trout (Oncorhynchus mykiss) during an outbreak on a fish farm. (i) Using an integrated approach, we characterized the pathogenesis of vibriosis from the morphological, hematological, and biochemical points of view. The molecular mechanisms associated with the host immune response were investigated using mass spectrometric analysis of trout plasma proteins. (ii) According to the severity of infection (the extent of tissue damage, the level of expression of pro-inflammatory genes, and changes in the leukocyte profile) three fish populations were identified among infected trout: fish with severe lesions (SL), fish with the moderate infectious process (IP) and asymptomatic fish (AS). (iii) Lymphopenia, granulocytosis, and splenomegaly were strong trends during the progression of infection and informative indicators of severe manifestation of disease, associated with hemorrhagic shock, metabolic acidosis, and massive tissue damage. (iv) As expected, pro-inflammatory interleukins, complement components, acute phase proteins, and antimicrobial peptides were implicated in the acute pathogenesis. Systemic coagulopathy was accompanied by increased antithrombotic reactions. (v) Reconstruction of metabolic pathways also revealed a high energy requirement for the immune response in severely affected fish. (vi) An unexpected result was a small difference between fish with moderate symptoms and fish with no or minor external signs of pathology (putatively resistant to infection). Increased production of antiproteases and enhanced blood coagulation cascade were observed in healthier fish, which may underlie the mechanisms of a controlled, non-self-damaging immune response to infection. (vii) Depending on the progression of the disease and the presence of the pathogen, a stepwise or linear change in the abundance of some plasma proteins was revealed. These proteins could be proposed as molecular markers for diagnosing the health and immune status of trout when cultured in fish farms.